Long‐term renal function after venoarterial extracorporeal membrane oxygenation. Issue 3 (8th January 2021) - Ayers, Brian; Bjelic, Milica; Kumar, Neil; Wood, Katherine; Barrus, Bryan; Prasad, Sunil; Gosev, Igor
Abstract: Background: The utilization of venoarterial extracorporeal membrane oxygenation (VA‐ECMO) as a life‐supporting therapy has increased exponentially over the last decade. As more patients receive and survive ECMO, there are a number of unanswered clinical questions about their long‐term prognosis and organ function including the need for long‐term dialysis. Methods: We aimed to utilize over 208 patient‐years of follow‐up data from our large institutional cohort of VA‐ECMO patients to determine the incidence of requiring VA‐ECMO support on the need for renal replacement therapy after discharge (LT‐dialysis). This retrospective review included all adult VA‐ECMO patients at our institution from January 2014 to October 2018 ( N = 283). Results: Out of the 99 (35%) survivors, 88 (89%) did not require LT‐dialysis of any duration after discharge from the index hospitalization. Patients who required VA‐ECMO for decompensated cardiogenic shock were more likely to need LT‐dialysis ( p = .034), and those who required renal replacement therapy during VA‐ECMO ( N = 27) also had a higher incidence of LT‐dialysis (33%). Conclusion: Overall, these data suggest there is a low incidence of long‐term dialysis dependence among survivors of VA‐ECMO support. Worries about the potential long‐term detrimental effect of VA‐ECMO should not preclude patients from receiving this life‐saving support.